Työntekijöiden kokemuksia teknostressistä työyhteisöviestinnässä - Hämäläinen, Vilma (2025)
This study focuses on employees' experiences of technostress in organizational communication. The aim of the study was to explore the communication practices present in the target organization and to identify which aspects of organizational communication influence the experience of technostress. The theoretical framework was built around workplace communication, the characteristics of the digital work environment, and existing research on technostress. The connection between these themes assumed that technostress arises from the interaction between individual and organizational factors. The study was con-ducted as a case study using ethnographic research methods. The selected case was a department within the organization where the similarity of work tasks allowed for a reliable analysis of communication practices. The research data consisted of Microsoft Teams usage statistics as well as observations and inter-view-based data. According to the results, the most significant source of technostress was information overload, which stemmed from both individual (e.g., cognitive) and organizational (e.g., overlapping and constantly changing in-formation) factors. This overload led to behaviors such as selective attention to messages, information avoidance, and difficulties in information retrieval. Additionally, digital communication revealed signs of distrust toward the employer organization and challenges in team collaboration under hybrid work conditions. Despite these challenges, the study also highlighted positive communication practices such as an open discussion culture and a general willing-ness to help each other. These aspects could be further strengthened by clarifying employer expectations regarding communication and by establishing common communication practices and tools. The study focused specifically on communication-related technologies, leaving out the effects of other technological tools.